Large‐Grained Perovskite Films Enabled by One‐Step Meniscus‐Assisted Solution Printing of Cross‐Aligned Conductive Nanowires for Biodegradable Flexible Solar Cells. Issue 35 (2nd August 2020) - Qi, Jiabin; Chen, Shuo; Lan, Chuntao; Wang, Aurelia Chi; Cui, Xun; You, Zhengwei; Zhang, Qinghong; Li, Yaogang; Wang, Zhong Lin; Wang, Hongzhi; Lin, Zhiqun
Abstract: Increasing performance demand associated with the short lifetime of consumer electronics has triggered fast growth in electronic waste, leading to serious ecological challenges worldwide. Herein, a robust strategy for judiciously constructing flexible perovskite solar cells (PSCs) that can be conveniently biodegraded is reported. The key to this strategy is to capitalize on meniscus‐assisted solution printing (MASP) as a facile means of yielding cross‐aligned silver nanowires in one‐step, which are subsequently impregnated in a biodegradable elastomeric polyester. Intriguingly, the as‐crafted hybrid biodegradable electrode greatly constrains the solvent evaporation of the perovskite precursor solution, thereby generating fewer nuclei and in turn resulting in the deposition of a large‐grained dense perovskite film that exhibits excellent optoelectronic properties with a power conversion efficiency of 17.51% in PSCs. More importantly, the hybrid biodegradable electrode‐based devices also manifest impressive robustness against mechanical deformation and can be thoroughly biodegraded after use. These results signify the great potential of MASP for controllably assembling aligned conductive nanomaterials for biodegradable electrodes. As such, it represents an important endeavor toward environmentally friendly, multifunctional and flexible electronic, optoelectronic, photonic, and sensory materials and devices. Abstract : A robust strategy for constructing flexible perovskite solar cells that can be conveniently biodegraded is introduced. The results signify the great potential of meniscus‐assisted solution printing for controllably assembling aligned conductive nanomaterials for biodegradable electrodes. As such, it represents an important endeavor toward environmentally friendly, multifunctional, and flexible electronics.